3D sponges of chemically functionalized chitosan for potential environmental pollution remediation: biosorbents for anionic dye adsorption and 'antibiotic-free' antibacterial activity. Issue 13 (7th June 2021) - Carvalho, Isadora C.; Medeiros Borsagli, Fernanda G. L.; Mansur, Alexandra A. P.; Caldeira, Cláudia L.; Haas, Dionei J.; Lage, Andrey P.; Ciminelli, Virginia S. T.; Mansur, Herman S.
ABSTRACT: In this work, it was developed three-dimensional (3D) porous hydrogel sponges produced by the freeze-dried process using chitosan polymer functionalized by 11-mercaptoundecanoic acid (MUA). These chitosan-based sponges were used as cationic adsorbents for the removal of anionic methyl orange (MO) dye, simulating a model organic pollutant in aqueous medium. Moreover, these porous 3D constructs were also evaluated as 'antibiotic-free' antibacterial materials against gram-negative and gram-positive bacteria, Pseudomonas aeruginosa and Staphylococcus aureus, respectively, which were used as model pathogens possibly found in contaminated hospital discharges. These 3D hydrogels were comprehensively characterized through morphological methods such as scanning electron microscopy and X-ray micro-computed tomography techniques, combined with FTIR, Raman, and UV-visible spectroscopy analyses. Additionally, the surface area, the degree of swelling, and the adsorption profiles and kinetics of these scaffolds were systematically investigated. The chemically thiolated chitosan (CHI-MUA) hydrogels were successfully produced with a supramolecular polymeric network based on hydrogen bonds, disulfide bonds, and hydrophobic interactions that resulted in higher stability in aqueous medium than hydrogels of pristine chitosan. CHI-MUA exhibited sponge-like three-dimensional structures, with highly interconnected and hierarchical pore size distribution with high porosity and surface area. These architectural aspects of the 3D sponges favoured the high adsorption capacity for MO dye (∼388 mg.g −1 ) in water with removal efficiency greater than 90% for MO solutions (from 20 mg.L −1 –1200 mg.L −1 ). The adsorption data followed a pseudo-second-order kinetic model and adsorption isotherm analysis and spectroscopy studies suggested a multilayer behaviour with coexistence of adsorbent-adsorbate and adsorbate-adsorbate interactions. Additionally, the in vitro evaluation of toxicity (MTT and LIVE-DEAD® assays) of 3D-sponges revealed a non-toxic response and preliminary suitability for bio-related applications. Importantly, the 3D-sponges composed of chitosan-thiolated derivative proved high antibacterial activity, specificity against P. aeruginosa (model hazardous pathogen), equivalent to conventional antibiotic drugs, while no lethality against S. aureus (reference commensal bacteria) was observed. GRAPHICAL ABSTRACT: UF0001